2016
DOI: 10.7897/2277-4343.075226
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Twelve Weeks Sri Vishnu Sahasranama Chanting on Stress, Cognition and Autonomic Functions: A Pilot Study

Abstract: Vishnu Sahasranama means 1000 names of Lord Sri Maha Vishnu. The 1000 names are in the 108 slokas are segregated and recited individually. In the present study, we have observed the effectiveness of Vishnu Sahastra nama chanting for stress management in a research scholar. The participant was given a training session of pronouncing the namas by Sanskrit expert for week days. After that he started chanting Sri Vishnusahastram every day at 8 am for 12 weeks. DASS-42 questionnaire and serum cortisol was used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Ajay A Gurjar and Sidhartha L. et al [5], [6] during 2008 and 2016 performed FFT analysis of power versus frequency of the signal energies associated with OM. The findings suggested that OM shall be considered as a cosmic sound and the totality of all sounds.…”
Section: Fig 1 Digital Spectal Analysis For Male and Female Voice Omentioning
confidence: 99%
“…Ajay A Gurjar and Sidhartha L. et al [5], [6] during 2008 and 2016 performed FFT analysis of power versus frequency of the signal energies associated with OM. The findings suggested that OM shall be considered as a cosmic sound and the totality of all sounds.…”
Section: Fig 1 Digital Spectal Analysis For Male and Female Voice Omentioning
confidence: 99%
“…They affect the psyche and reach subliminal levels where our karmic patterns are preserved. The best possible recitation of the mantras can diminish stress and pressure [5].…”
Section: Introductionmentioning
confidence: 99%